ASSESSMENT OF E-PROCUREMENT SUBJECTS' MISSTEPS FOR CONSTRUCTION AND CONSULTANCY SERVICES THROUGHOUT THE SURABAYA CITY AREA AS AN EDUCATIONAL ADJUNCT FOR PROJECT TENDER COURSES - Gde Agus Yudha Prawira Adistana; Mas Suryanto HS; Purwo Mahardi; Mochamad Firmansyah Sofianto (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
From the government's perspective, an electronic tender or e-tendering system in the procurement of goods and services in Indonesia is a platform to acknowledge good governance and public services since it enhances cost efficiency, effectiveness, shorter turnaround periods, delivers excellent public monitoring, fosters competitiveness, and increases government accountability. Nevertheless, numerous tenders have managed to fail during the implementation of e-tendering for construction works. The purpose of this study is to identify the factors that contribute to tender failures throughout the Surabaya City area. The factors that contributed to the tender's failure were identified from the results of the 220 construction tenders stated on the LPSE website. Descriptive statistical analysis was used to obtain factors that cause e-tender failures from the data obtained. Administrative, technical, price, and qualification criteria are the most dominant four failure criteria. The most apparent cause for auction failure is the provider's inability to attach references to previous projects.